Land Use Intensity, Crop Diversification and Productivity of Farmers in Akinyele Local Government Area of Oyo State, Nigeria (2020)
This study examined the relationship between land use intensity, crop diversification and productivity of farmers in Akinyele Local Government Area, Oyo State, Nigeria. A total of 200 respondents were selected proportionate to size from four communities and structured questionnaire was used to collect data. Data were analyzed using Descriptive Statistics, Ruthenberg index, Herfindahl index, Total Factor productivity and Tobit regression analysis. The mean age of farmers was found to be 50.9years (±15.2), 93.0% were male, 88.0% were married, having an average of 6 persons per household, and 71.5% had formal education. Also, farmers had an average of 25 years of experience in farming, majority (86.5%) were primarily into farming, and 19.5% were members of farmers’ association. Majority (79.5%) used hired labour for their farming activities and 25.5% had access to other sources of income asides farm income, 2.0% had access to credit, while 9.0% had access to extension services. Most (51.0%) of the farmers got their land through inheritance while 12.0% rented theirs. The study showed that only 30.0% of the respondents practiced bush fallow, and mean land use intensity of 0.9(±0.2) indicates that land is intensively used in the study area. Majority (72.5%) of the respondents practiced mixed cropping, planted an average of 2 crops, and cultivated an average farm size of 4.6ha. The results of Herfindahl index showed a mean of 0.7(±0.3) which implies that farmers practiced crop diversification while 27.5% practiced specialization (planting only 1 crop). More than half (59.5%) of the farmers had TFP>1 which indicates low productivity. Tobit regression results show that Herfindahl index was found to be positively related to productivity at 1%, implying that crop diversification reduces the level of productivity. At 5% level of significance, age had negative significant effect (-0.01) while access to credit had positive significant effect (01.26) on the level of productivity. Land use intensity was however found to influence productivity positively, though not significantly. It was concluded that crop specialization increases the level of productivity. Crop specialization should be encouraged among farmers with good land management practices to help reduce the negative effect that high land use intensity might cause in the future.